2023
DOI: 10.5217/ir.2021.00154
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rates for hospitalized infections, herpes zoster, and malignancies in patients with ulcerative colitis in Japan: an administrative health claims database analysis

Abstract: Patients with UC are at an increased risk of infection and malignancy, which is partly inherent to the disease itself 5 but also due to the therapies used in the management of UC, or a combination of these factors. 6,7 Therapies used for disease control, such as corticosteroids, immunosuppressants (azathioprine and 6-mercaptopurine [6-MP]), calcineurin inhibitors, and tumor necrosis factor inhibitors (TNFi; infliximab, adalimumab, and golimumab), have a primary function in the inhibition and control of immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“… 4 29 30 Furthermore, a recent study has reported that patients with UC who were administered calcineurin inhibitors had higher incidence rate of infections requiring hospitalization, herpes zoster, and malignancies than those not administered these therapies. 31 However, most patients in this study received tacrolimus, followed by tacrolimus and mycophenolate mofetil, as immunosuppressive agents after transplantation. No association with safety or prognosis was observed in patients with IBD after transplantation.…”
Section: Discussionmentioning
confidence: 97%
“… 4 29 30 Furthermore, a recent study has reported that patients with UC who were administered calcineurin inhibitors had higher incidence rate of infections requiring hospitalization, herpes zoster, and malignancies than those not administered these therapies. 31 However, most patients in this study received tacrolimus, followed by tacrolimus and mycophenolate mofetil, as immunosuppressive agents after transplantation. No association with safety or prognosis was observed in patients with IBD after transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…The claims-based algorithms, developed with expert input, identified cohorts of patients with demographics and clinical characteristics as expected for these infectious diseases. Other retrospective claims database studies in Japan used algorithms with ICD-10 diagnosis codes only [ 21 ], or ICD-10 diagnosis codes plus claims data regarding prescription medication [ 2 , 22 ]. These studies did not validate the algorithms using clinical information.…”
Section: Discussionmentioning
confidence: 99%
“…The data contains routinely collected information on the following items for patients with COVID-19 until December 31, 2021: age; sex; diagnoses based on the International Classi cation of Diseases Tenth Revision (ICD-10) codes [18]; daily medical procedures and medications; discharge summary including body weight, height, and date of hospital admission and discharge; and survival status. There have been many clinical studies for COVID-19 or infectious diseases in recent years using data from MDV [19][20][21]. We described several demographic characteristics of patients with COVID-19 from MDV data compared with those from publicly available data for COVID-19 by the Japanese Ministry of Health, Labor and Welfare (MHLW) [22] (Supplementary Fig.…”
Section: Study Design and Data Sourcementioning
confidence: 99%